1998
DOI: 10.1115/1.2841415
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Periodic Ribs on the Local Aerodynamic and Heat Transfer Performance of a Straight Cooling Channel

Abstract: The local aerodynamic and heat transfer performance were measured in a rib-roughened square duct as a function of the rib pitch to height ratio. The blockage ratio of these square obstacles was 10 or 20 percent depending on whether they were placed on one single (1s) or on two opposite walls (2s). The Reynolds number, based on the channel mean velocity and hydraulic diameter, was fixed at 30,000. The aerodynamic description of the flow field was based on local pressure distributions along the ribbed and adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
74
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(90 citation statements)
references
References 15 publications
16
74
0
Order By: Relevance
“…There is a good agreement between measured and calculated recirculation lengths. The recirculation lengths predicted by the EVM and NLEVM2 are about 4.5 and 4.8 times the rib height, respectively, which are close to the measured value of 4.3 times of the rib height reported by Rau et al (1998). Mean flow predictions for the ribbed channel at Re ¼ 122; 400 indicated that increasing Reynolds number has insignificant effects on the flow features.…”
Section: Resultssupporting
confidence: 81%
“…There is a good agreement between measured and calculated recirculation lengths. The recirculation lengths predicted by the EVM and NLEVM2 are about 4.5 and 4.8 times the rib height, respectively, which are close to the measured value of 4.3 times of the rib height reported by Rau et al (1998). Mean flow predictions for the ribbed channel at Re ¼ 122; 400 indicated that increasing Reynolds number has insignificant effects on the flow features.…”
Section: Resultssupporting
confidence: 81%
“…The quantity Nu=Nu 0 indicates the heat transfer enhancement compared to that of flow over a flat plate. For all models, agreement with the measurements of [33,6] is observed. At each end of Fig.…”
Section: Heat Transfersupporting
confidence: 83%
“…The geometry of [33] is comparable (h=D ¼ 0:1 and D=h ¼ 9) with the current study (h=D ¼ 0:1 and D=h ¼ 10). The additional Re ¼ 30; 000 data of [6] provides a comparison between the different experimental facilities.…”
Section: Modelsupporting
confidence: 58%
See 1 more Smart Citation
“…They concluded that a pitchto-height ratio of 8.5 consistently produced the highest rib average heat transfer coefficients. Rau et al [7] used a liquid-crystal technique to measure the local heat transfer distribution in a square duct. They performed flowfield measurements by using a two-dimensional laser Doppler velocimetry system and showed that the boundary-layer separation and reattachment contributed to the heat transfer enhancement in the ribbed channel.…”
mentioning
confidence: 99%